ANALISIS FITOKIMIA DAN UJI POTENSI EKSTRAK BUAH RENGGAK (Amomum Dealbatum) SEBAGAI PESTISIDA NABATI TERHADAP JAMUR Pyricularia Oryzae DAN BAKTERI Xanthomonas oryzae - Novita Hidayatun Nufus (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to determine the potency of Renggak (Amomum dealbatum) extract as bio pesticide against Pyricularia oryzae and Xanthomonas oryzae. Therefore an in vitro of  antifungal and antibacterial activity of the Renggak ethanol extract were carried out against Pyricularia oeyzae and Xanthomonas oryzae. In vitro antifungal  analysis were done using agar diffusing method by dissolving Renggak extract (1%, 5%, and 10%) into fungal medium and the growth of  Pyricularia oryzae were observed. In vitro antibacterial analysis were complited using agar diffusing method with paper disk that contain Renggak extract (10%, 20%, and 30%) and antibiotic chloroamfenikol as positive control. The result suggest that Renggak fruit extract has antifungal and antibacterial activities. The treatment with 10% Renggak extract could inhibit the growth of Pyricularia oryzae to 100%, same with positive control (Fungicide Score-250). In vitro test for antibacterial activity showed that treatments with 20% and 30% Renggak extract gave inhibitory activities that similar with positive control. Renggak ethanol extract gave positive results on Flavonoid, Alkaloid, Steroid, Terpenoid, and Saponin tests. GC-MS assays showed that Renggak ethanol extract produces at least 10 organic compounds that was identified as  2-butanone, 4-methoxypheyl, Benzenepropanoic-aci, 4-hydroxyphenil, CAS, octadecanoid acid, stearic acid, palmiti acid, Benzenepropanoic acid, dan Farnesol isomer A, which have antimicrobial avtivities.